If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+3-2=x+6
We move all terms to the left:
3x+3-2-(x+6)=0
We add all the numbers together, and all the variables
3x-(x+6)+1=0
We get rid of parentheses
3x-x-6+1=0
We add all the numbers together, and all the variables
2x-5=0
We move all terms containing x to the left, all other terms to the right
2x=5
x=5/2
x=2+1/2
| 2/3(x-7)=2 | | 5x=6,5-(x-5)² | | 7+x/0.5=2 | | 5m+30=-2m-19 | | 1/2(x-5)(x-14)=35 | | X(2-√2)=(4-x)(x²-x) | | 9=3/2v | | 7/6x=1/6 | | 6t+10=5 | | 2(x-1)+4=7(2x+3)-5 | | d5.5=4;22.23.24 | | 2x+35=5x-7 | | 27=y/3-16 | | 2^x=18^6 | | w/9=0.9 | | 3-(1-2x)=10-x | | 7.5h+10=6.25(h−3) | | k^2=0.49k | | 7.5h=6.25(h−3)+10 | | 6(x-4)+7=2(x+4) | | 11+3x-3=8x+7-5x | | 2x+31=(x+13)+7 | | –9u=45 | | 7p-1=5 | | 4.5x=18;3.4.5 | | 6(x−4)+7=2(x+4) | | 5(2x-1)=x+6 | | 20a-8a-16a14a+18a=16 | | -3+5n=2n+15 | | 26w+5w^2-24=0 | | 13s-2s-5s=12 | | X+11+7=2×+18x=-18 |